2014
DOI: 10.1002/ejoc.201403284
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Cyclopropanation of Strained Alkenes with 3‐Pinacolatoboryl‐1‐arylallyl Carboxylates

Abstract: The palladium‐catalyzed cyclopropanation of strained alkenes with 3‐pinacolatoboryl‐1‐arylallyl carboxylates was explored. The reactions proceeded smoothly under mild conditions, and the cyclopropanation products were obtained in good to high yields with high diastereoselectivities if CsF, 18‐crown‐6, and molecular sieves were used as additives. The reaction was hypothesized to proceed through the formation of a putative palladacyclobutene intermediate that needed to be considered to explain the observed stere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…In our recent studies, we demonstrated the distinct reactivities of allylic gem -palladium/metalloid intermediates that could serve as C3 units in reactions other than allylation reactions. For example, we have reported the stereoselective cyclopropanation of strained alkenes by the Pd-catalyzed reaction of 1 (Scheme ) . Furthermore, a Pd-stabilized vinylcarbene intermediate B was formed from A , and it can be used in the carbene dimerization .…”
mentioning
confidence: 99%
“…In our recent studies, we demonstrated the distinct reactivities of allylic gem -palladium/metalloid intermediates that could serve as C3 units in reactions other than allylation reactions. For example, we have reported the stereoselective cyclopropanation of strained alkenes by the Pd-catalyzed reaction of 1 (Scheme ) . Furthermore, a Pd-stabilized vinylcarbene intermediate B was formed from A , and it can be used in the carbene dimerization .…”
mentioning
confidence: 99%
“…During the course of a study aimed at exploring the palladium‐catalyzed cyclopropanation of strained cycloalkenes with borylated allyl benzoates, the boryl group was found to affect the diastereoselectivity (Scheme 5). [32] The partially formed palladium‐complexed vinylcarbene species likely led to a decline in the diastereoselectivity. Interestingly, the combination of CsF and 18‐crown‐6 (18‐C‐6) as additives effectively promoted the cyclopropanation reaction and played a key role in the enhancement of diastereoselectivity in this reaction.…”
Section: Cyclopropanation Of Strained Cycloalkenesmentioning
confidence: 99%
“…As described above, organosilyl‐substituted π‐allylpalladium species exhibited unique reactivities in addition to those in simple allylation reactions, such as stereoselective cyclopropanation of strained cycloalkenes [27,32] and carbene dimerization [33] . Critical to the efficacy of the latter process was the cognition that the ancillary ligand on palladium could be altered to the prevent formation of a putative palladacyclobutene species.…”
Section: Palladium‐catalyzed Generation Of αγ‐Disubstituted Allylsilanesmentioning
confidence: 99%